Desarrollo y escalado del proceso de producción de un queso de pasta blanda light funcional debido a la incorporación de fitoesteroles y alfa-tocoferol - Rizzo, Sergio Anibal (2023)
The objective was to study the shelf life and monitor the oxidative parameters of salut light cheeses added with phytosterols (EF) and natural tocopherols (TF) produced on a pre-commercial industrial scale, which were obtained in the SME plant. CDS – Lácteos Capilla del Señor S.A. (Villa María, province of Córdoba). The evaluation was carried out on light functional cheese that contained 2.2 g of free EF in a 60g portion. Given that the EF used provide a high concentration of polysaturated fatty acids, an excess of lipids susceptible to oxidation is generated. To prevent this, the addition of alpha-tocopherol from a natural source as an antioxidant was chosen.